The Procession that Travels Inside: Yuyachkani's "Santiago" - Miguel Rubio Zapata (Studies in 20th & 21st Century Literature, 2008)
In collaborative theater projects like Yuyachkani, it is hard to define the exact moment when a new project begins. Generally we have a very imprecise idea as our initial point of departure and we explore it more fully in the day-to-day work, where it changes a great deal. Santiago is a project that began as a processional performance piece in the public plazas before premiering as a theatrical work in its current form, as a largely Quechua-language play focusing on permutations of faith in an almost uninhabited Andean village. The final project arrived as a result of this complex process of research and exploration. Santiago has a very long road to its current form, always with the indispensable accompaniment of the writer Peter Elmore, the co-author of the play.
Keywords: Ecuadorian theatre; Ecuador; Quechua; Andean village; collaborative theatre; Santiago; processional performance; Peter Elmore